WHO disability grade does not influence physical activity in Brazilian leprosy patients - Do Prado, Glauber Dias; Ruiz Prado, Renata Bilion; Camargo Marciano, Lucia Helena Soares; Tonelli Nardi, Susilene Maria; Cordeiro, Jose Antonio; Monteiro, Henrique Luiz [UNESP] (Lepra, 2011)
Disability caused by leprosy may be associated with stigma. The aim of this work is to describe the degree of disability, quality of life and level of physical activity of individuals with leprosy and to identify possible correlations between these factors. Ninety-seven patients from two referral centres were studied. A complete medical history was taken and the World Health Organization degree of physical disability classification (WHO-DG), the International Physical Activity Questionnaire (IPAQ) and the Medical Outcome Study 36-item Short-form health Survey (SF36) were applied. The mean age of patients was 51 +/- 14.9 years old; participants were predominantly men, married, unemployed, had concluded treatment and had had lepromatous leprosy. The WHO-DG and the level of physical activity (P-value = 0.36) were not correlated. The WHO-DG showed that 72.2% of patients had disabilities, 37-1% of whom performed vigorous physical activities. No significant association was observed between the WHO-DG and the domains of the QoL SF-36 except for functional capacity (P-value = 0.02); the physical capacity is generally 'very good' when individuals have no disabilities and 'bad' with severe disabilities. In conclusion, the WHO-DG of leprosy patients does not affect the level of physical activities or quality of life except functional capacity. There is no significant association between physical activities and quality of life in these individuals.